Experimental assessment of gold nanoparticle-mediated dose enhancement in radiation therapy beams using electron spin resonance dosimetry. (19th May 2015) - Wolfe, T; Guidelli, E J; Gómez, J A; Baffa, O; Nicolucci, P
Abstract: In this work, we aim to experimentally assess increments of dose due to nanoparticle-radiation interactions via electron spin resonance (ESR) dosimetry performed with a biological-equivalent sensitive material. We employed 2-Methyl-Alanine (2MA) in powder form to compose the radiation sensitive medium embedding gold nanoparticles (AuNPs) 5 nm in diameter. Dosimeters manufactured with 0.1% w/w of AuNPs or no nanoparticles were irradiated with clinically utilized 250 kVp orthovoltage or 6 MV linac x-rays in dosimetric conditions. Amplitude peak-to-peak (App) at the central ESR spectral line was used for dosimetry. Dose-response curves were obtained for samples with or without nanoparticles and each energy beam. Dose increments due to nanoparticles were analyzed in terms of absolute dose enhancements (DEs), calculated as App ratios for each dose/beam condition, or relative dose enhancement factors (DEFs) calculated as the slopes of the dose-response curves. Dose enhancements were observed to present an amplified behavior for small doses (between 0.1–0.5 Gy), with this effect being more prominent with the kV beam. For doses between 0.5–5 Gy, dose-independent trends were observed for both beams, stable around (2.1 ± 0.7) and (1.3 ± 0.4) for kV and MV beams, respectively. We found DEFs of (1.62 ± 0.04) or (1.27 ± 0.03) for the same beams. Additionally, we measured no interference between AuNPs and the ESR apparatus, including the excitation microwaves, the magnetic fields and the paramagnetic radicals. 2MA was demonstrated to be a feasible paramagnetic radiation-sensitive material for dosimetry in the presence of AuNPs, and ESR dosimetry a powerful experimental method for further verifications of increments in nanoparticle-mediated doses of biological interest. Ultimately, gold nanoparticles can cause significant and detectable dose enhancements in biological-like samples irradiated at both kilo or megavoltage beams.